Cobalt sulfide loaded nickel oxide composite material with hollow regular hexahedron structure as well as preparation method and application of cobalt sulfide loaded nickel oxide composite material

By transforming cube-ZIF-67 into hollow nickel sulfide and loading nickel oxide nanoparticles, the method addresses the trade-off between cycle stability and capacitance in MOF materials, achieving improved electrochemical performance and structural integrity.

CN119694796APending Publication Date: 2025-03-25GUILIN UNIV OF ELECTRONIC TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411815589.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing methods for enhancing the electrochemical performance of MOFs materials either improve cycle stability by loading transition metals, which compromises capacitance, or increase capacitance by converting MOFs to transition metal oxides, but at the cost of reduced cycle stability due to structural issues.

Method used

A method involving the synthesis of a hollow nickel sulfide structure from cube-ZIF-67 via sol-gel and sulfurization, followed by loading nickel oxide nanoparticles onto the retained hollow structure, maintaining the high surface area and structural integrity of the initial MOF framework.

Benefits of technology

The approach results in a material with enhanced specific capacitance and cycle stability, retaining 80-90% of initial capacitance after 5000 cycles and achieving high energy density, while maintaining structural integrity and surface area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694796A_ABST
    Figure CN119694796A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt sulfide loaded nickel oxide composite material with a hollow regular hexahedron structure, which is prepared by the following steps: by taking C-ZIF-67 with a regular hexahedron structure as a substrate, performing etching by a solvothermal method to convert into cobalt sulfide CH-CoS with a hollow regular hexahedron structure; and then loading nickel oxide nanoparticles NiO on the hollow regular hexahedron structured cobalt sulfide CH-CoS through a solvothermal method and calcination to obtain CH-CoS / NiO. The preparation method comprises the following steps: 1, preparing the C-ZIF-67 with the regular hexahedron structure; 2, preparing CH-CoS with a hollow regular hexahedron structure; (3) preparation of CH-CoS / NiOH; and 4, preparing the CH-CoS / NiO with the hollow regular hexahedron structure. When the material is used as a supercapacitor electrode material, the mass specific capacitance is 1200-1300 F g <-1 >; 80-90% of the initial capacity is reserved after 5000 times of charge and discharge cycles; and the energy density is 30-40 Wh kg <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of supercapacitors, and in particular to a cobalt sulfide-loaded nickel oxide composite material with a hollow regular hexahedral structure, and a preparation method and application thereof. Background Art

[0002] Common materials in supercapacitor materials include organic metal framework materials MOFs and transition metal compounds. MOFs have the characteristics of high porosity and high specific surface area, so they have high energy storage capacity; in addition, the more important feature of MOFs is that there are many types of MOFs, such as ZIF-67, UIO-66, and MIL, which can adjust the microstructure. Among them, ZIF-67 has the characteristics of simple preparation method and high specific surface area, which is conducive to improving specific capacitance performance; in addition, ZIF-67 can also produce various microscopic morphologies according to different preparation methods. However, MOFs materials have the problem of poor electrochemical performance. Therefore, loading transition metal compounds on MOFs materials or converting MOFs materials into transition metal compounds can improve electrochemical performance.

[0003] Among them, the method of directly loading transition metal compounds on MOFs materials can significantly improve the cyclic stability of MOFs materials. For example, the existing literature 1 (Yuan Yuan, Chun Han et al. Structural energy storage composites based on etching engineering Fe-doped Co MOF electrode toward high energy density supercapacitors [J]. Journal of Power Sources, 2024, 609, 234688) loaded Fe-based amides on sheet Co-MOF by coprecipitation to produce a sheet structure composite material with rough particles on the surface. The electrode made of this material has a high conductivity at 1Ag -1 700C g -1 The specific capacity of the MOFs is 88%, and it still retains 88% of the specific capacity after 10,000 charge and discharge cycles. This technical solution directly loads transition metal compounds on the MOFs material, changes the electronic structure of Co in the Co-MOF through Fe-based amides, and improves stability, so that the composite material exhibits excellent cycle performance. However, since the morphology of the composite material is a rough triangular sheet structure, there is agglomeration between the sheets of this sheet structure during the cycle, which reduces the transfer rate of charge and electrons, and ultimately leads to a decrease in specific capacitance performance.

[0004] Another method is to directly convert MOFs materials into transition metal compounds to improve the specific capacitance performance of MOFs materials. For example, the existing literature 2 (Meng-Ke W, Chen C, et al. MOF-derived hollow double-shelled NiO nanospheres for high-performance supercapacitors [J]. Journal of Alloys and Compounds 734 (2018) 1-8) first synthesizes spherical Ni-MOF precursors by a one-step hydrothermal method, and then calcines them at 400 ° C to prepare hollow NiO nanospheres with spherical structures. At 0.5Ag -1 At a current density of 473F g -1 The specific capacitance of MOFs is 94% after 3000 cycles. This technical solution directly converts MOFs materials into transition metal oxides by calcination, thereby improving the specific capacity of MOFs materials. However, the obtained hollow nano-microspheres are multi-layer structures, which have a volume expansion phenomenon during the charge and discharge cycle, resulting in the collapse of the microscopic morphology, which leads to a decrease in cycle performance.

[0005] From the above analysis, it can be seen that the two technical solutions each have technical problems, which can be simply summarized as follows: if transition metal compounds are directly loaded on MOFs materials, although the cycle performance of the material can be significantly improved, the specific capacitance performance is poor; if MOFs materials are directly converted into transition metal compounds, although the specific capacitance performance can be improved, the cycle performance is poor.

[0006] Therefore, combining the above two schemes, that is, combining loading and conversion at the same time, can improve the specific capacitance and cycle performance of MOFs materials. For example, the existing document 3 (Jiaxi X, Hao G, et al. Hollow Ni3S4@Co3S4 with core-satellite nano-structure derived from metal-organic framework (MOF)-on-MOF hybrids as an electrode material for supercapacitors [J]. The Royal Society of Chemistry, 2024, 53, 4479-4491.) uses a two-step hydrothermal method to prepare a regular dodecahedral ZIF-67 precursor loaded on a spherical Ni-MOF; then, by sulfurization, the precursor is made into a Ni3S4@Co3S4 with a hollow structure. The electrode is 1Ag -1The specific capacity is 747.3C g -1 , and after 5000 cycles, it still maintains 85.4% of the initial capacity. This technical solution significantly improves the specific capacitance performance and cycle stability of the composite material by first loading another MOF material on the MOF material to form a multi-element precursor, and then converting the precursor into a transition metal sulfide by sulfurization, that is, first loading a transition metal base on the MOFs material and then converting it into a transition metal compound. However, the technical problem of this technical solution is that ZIF-67 has a regular dodecahedral structure and Ni-MOF has a spherical structure. When the ZIF-67 with a regular dodecahedral structure is loaded on the spherical Ni-MOF to prepare a precursor, uneven loading and even agglomeration occur, resulting in a reduction in active sites, and ultimately a decrease in specific capacitance performance.

[0007] For example, the existing literature 4 (Wenrui Wu, Yue Yan, et al. Interface construction of CuCoSe@NiS based on an ultrathin nanosheet for high-performance supercapacitors [J]. Journal of Materials Chemistry A, 2024) uses a two-step solvothermal method to first convert CoCu-MOF into a sheet of selenide; then, NiS nanosheets are loaded to form a honeycomb sheet structure. The electrode is -1 The specific capacity is up to 2937.6F g -1 , 80% of the initial capacity was retained after 5000 cycles; the assembled asymmetric supercapacitor was -1 It can provide 41.8W h kg -1 High energy density. This technical solution adopts the method of first selenizing the MOFs material and then loading NiS nanosheets, so that the electrode material exhibits excellent specific capacitance performance, that is, first converting the MOFs material into a transition metal compound and then loading other transition metal compounds. However, the technical problem of this technical solution is that the morphology of the obtained composite material is a honeycomb structure of stacked sheets. Therefore, there are problems of local stress changes and volume changes during the cycle process, which directly leads to the problem of microscopic morphology collapse during long-term cycles, and ultimately leads to a decrease in cycle performance.

[0008] It can be seen from existing documents 3 and 4 that converting MOFs materials into transition metal compounds or loading transition metal compounds on MOFs materials can improve electrochemical performance. At the same time, the order of the preparation method can significantly affect the specific capacitance performance.

[0009] In addition, the micromorphology also directly affects the specific capacitance performance. Summary of the invention

[0010] The purpose of the present invention is to provide a hollow hexahedral cobalt sulfide loaded nickel oxide composite material and a preparation method and application thereof.

[0011] According to the inventor's research, ZIF-67 with a regular hexahedral structure has a higher specific surface area than ZIF-67 with a conventional regular dodecahedral structure, that is, the specific capacitance performance can be improved. Based on the above research, the regular hexahedral ZIF-67 (Cube-ZIF-67) can be firstly sulfurized into a hollow regular hexahedral cobalt sulfide (CH-CoS) by a solvent thermal method, that is, on the basis of maintaining the original regular hexahedral structure, a hollow structure is obtained, and then, nickel oxide particles are loaded on the surface of the cobalt sulfide by a solvent thermal method and calcined to form a cobalt sulfide loaded nickel oxide composite material with a hollow regular hexahedral structure, by increasing the specific surface area, while improving the specific capacitance performance and cycle stability.

[0012] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:

[0013] A hollow hexahedral cobalt sulfide loaded nickel oxide composite material, which takes a hexahedral C-ZIF-67 as a substrate, is first etched by a solvothermal method to be converted into a hollow hexahedral cobalt sulfide CH-CoS, and then is loaded with nickel oxide nanoparticles NiO on the hollow hexahedral cobalt sulfide CH-CoS by a solvothermal method and calcination to obtain CH-CoS / NiO;

[0014] The microstructure of the C-ZIF-67 is a regular hexahedron structure, the microstructure of the CH-CoS is a hollow regular hexahedron structure; the microstructure of the CH-CoS / NiO is a hollow regular hexahedron structure, and nickel oxide particles are loaded on the surface;

[0015] The specific surface area of ​​CH-CoS is 15-25m 2 g -1 The pore size distribution is 4-6.5 nm, and the specific surface area of ​​CH-CoS / NiO is 45-55 m 2 g -1 , the pore size distribution is 1.4-9.6nm.

[0016] A method for preparing a hollow hexahedral cobalt sulfide-loaded nickel oxide composite material comprises the following steps:

[0017] Step 1, preparation of ZIF-67 with a regular hexahedral structure, first, dissolving cobalt nitrate hexahydrate and hexadecyltrimethylammonium bromide in deionized water to obtain a solution A, and at the same time, dissolving dimethylimidazole in deionized water to obtain a solution B, then quickly pouring the solution B into the solution A for mixing to obtain a solution C, then stirring the solution C under certain conditions, and finally, washing and centrifuging the obtained product with deionized water and anhydrous ethanol, and then vacuum drying under certain conditions to obtain Cube-ZIF-67 with a regular hexahedral structure, referred to as C-ZIF-67;

[0018] In the step 1, the mass ratio of aqueous cobalt nitrate, hexadecyltrimethylammonium bromide and dimethylimidazole is 60:1:900;

[0019] In step 1, the stirring conditions are as follows: the stirring temperature is 20-30°C and the stirring time is 10-30min; the drying conditions are as follows: the drying temperature is 50-70°C and the drying time is 11-13h;

[0020] Step 2, preparation of hollow hexahedral CH-CoS, first, dissolving the C-ZIF-67 obtained in step 1 in ethanol to obtain a D solution, then adding thioacetamide to the D solution, performing a hydrothermal reaction under certain conditions, sulfiding and etching the C-ZIF-67, and after the hydrothermal reaction is completed, vacuum drying the hydrothermal reaction product under certain conditions to obtain a hollow hexahedral Cube-Hollow-Co3S4, referred to as CH-CoS;

[0021] In the step 2, the mass ratio of C-ZIF-67 to thioacetamide is 1:1.5;

[0022] In step 2, the conditions for the hydrothermal reaction are: the hydrothermal temperature is 110-130° C., and the hydrothermal time is 3-5 hours; the conditions for the drying are: the drying temperature is 50-70° C., and the drying time is 11-13 hours;

[0023] Step 3, preparation of CH-CoS / NiOH, first, dissolving the CH-CoS obtained in step 2 in deionized water to obtain solution E, then adding nickel nitrate hexahydrate and urea to solution E and stirring sufficiently to obtain solution F, then subjecting solution F to a hydrothermal reaction under certain conditions, and after the hydrothermal reaction is completed, vacuum drying the hydrothermal reaction product under certain conditions to obtain CH-CoS / NiOH;

[0024] In step 3, the mass ratio of CH-CoS, nickel nitrate hexahydrate and urea is 5:6:6;

[0025] In step 3, the conditions for the hydrothermal reaction are: the hydrothermal temperature is 110-130° C., and the hydrothermal time is 5-7 hours; the conditions for the drying are: the drying temperature is 50-70° C., and the drying time is 11-13 hours;

[0026] Step 4, preparation of hollow hexahedral CH-CoS / NiO, under certain conditions, calcining the CH-CoS / NiOH obtained in step 3 to obtain a hollow hexahedral cobalt sulfide loaded nickel oxide composite material CH-CoS / NiO, referred to as CH-CoS / NiO;

[0027] In step 4, the calcination conditions are: in air, the calcination temperature is 200-400° C., and the calcination time is 1-3 hours.

[0028] When the hollow hexahedral cobalt sulfide loaded nickel oxide composite material is used as a supercapacitor electrode material, it is charged and discharged in the voltage window range of 0-0.5V. -1 When the mass specific capacitance is 1200-1300F g -1 ; At a current density of 10A g -1 When the battery is charged and discharged for 5,000 times, it still retains 80-90% of its initial capacity.

[0029] When used as a supercapacitor device, it can be assembled with activated carbon at a power density of 800W kg -1 The energy density is 30-40Wh kg -1 .

[0030] The technical effects of the present invention have been tested experimentally, and the specific contents are as follows:

[0031] The present invention has been tested by XRD and found that CH-CoS / NiO has characteristic peaks of Co3S4 and NiO, which means that the CH-CoS / NiO composite structural material is successfully prepared.

[0032] According to the SEM test, the microstructure of CH-CoS is a regular hexahedron structure with a rough surface, and the microstructure of CH-CoS / NiO is a regular hexahedron structure with a rough surface. NiO particles are loaded on the surface.

[0033] The BET test shows that the specific surface area of ​​CH-CoS is 15-25m 2 g -1 The pore size distribution is 4-6.5nm. The specific surface area of ​​CH-CoS / NiO is 45-55m 2 g -1 , the pore size distribution is 1.4-9.6nm.

[0034] The present invention is tested by three-electrode electrochemical detection, and it is known that in 6M KOH solution, the charging and discharging is carried out in the window voltage range of 0-0.5V, and the charging and discharging is carried out in the window voltage range of 1Ag -1 At a current density of 1.34 W, the mass specific capacitance of the CH-CoS / NiO composite material is 1200-1300 F g -1 . In 10Ag -1 At a current density of , the CH-CoS / NiO composite structure material retains 80-90% of the initial specific capacitance after 5000 cycles of charge and discharge.

[0035] The present invention has been tested by double-electrode electrochemical detection. It is found that in 6M KOH solution, the CH-CoS / NiO composite material is charged and discharged at a window voltage of 0-1.6V at 800W kg -1 The power density is 30-40Wh kg -1 energy density.

[0036] Therefore, the CH-CoS / NiO composite structural material of the present invention has the following advantages over the prior art:

[0037] 1. Both CH-CoS and NiO nanoparticles have high theoretical specific capacitance, and the synergistic effect is achieved by compounding the two materials, thereby improving the high specific capacitance performance;

[0038] 2. The framework structure advantages of C-ZIF-67 are fully utilized. By making C-ZIF-67 into CH-CoS, the regular hexahedral structure of C-ZIF-67 is retained, and NiO nanoparticles are loaded on CH-CoS, which ultimately increases the specific surface area of ​​the composite material; improves the specific capacitance performance and cycle stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The XRD test diagrams of Example 1 and Comparative Example 1 are shown below;

[0040] Figure 2 This is the XPS test image of Example 1;

[0041] Figure 3 This is a SEM test image of C-ZIF-67 prepared in Example 1 at 4 μm;

[0042] Figure 4 This is a SEM test image of CH-CoS prepared in Example 1 at 1 μm;

[0043] Figure 5 This is a SEM test image of CH-CoS / NiO prepared in Example 1 at 100nm;

[0044] Figure 6TEM test image and EDS test image of CH-CoS / NiO prepared in Example 1 at 100nm;

[0045] Figure 7 is the pore size distribution diagram of Example 1;

[0046] Figure 8 is a N2 isothermal adsorption / desorption curve diagram of Example 1;

[0047] Fig. 9 For Example 1 at 1Ag -1 Charge and discharge curves under current density;

[0048] Fig.10 The cycle performance diagrams of Example 1 after 5000 cycles and Comparative Example 2 after 1000 cycles;

[0049] Fig.11 is the Lagun diagram of Example 1;

[0050] Fig.12 This is the SEM test image of D-ZIF-67 prepared in Comparative Example 1 at 100 nm;

[0051] Fig.13 D-ZIF-67 prepared in Comparative Example 1 was prepared at 1Ag -1 Charge and discharge curves under current density;

[0052] Fig.14 This is the SEM test image of NiCo-LDH prepared in Comparative Example 2 at 1 μm;

[0053] Fig.15 NiCo-LDH prepared in Comparative Example 2 was prepared at 1Ag -1 Charge and discharge curves under current density; DETAILED DESCRIPTION

[0054] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0055] Example 1

[0056] A method for preparing a hollow hexahedral cobalt sulfide-loaded nickel oxide composite material comprises the following steps:

[0057] Step 1, preparation of hexahedral ZIF-67, first, dissolving 0.6g of cobalt nitrate hexahydrate and 0.01g of hexadecyltrimethylammonium bromide in 20mL of deionized water to obtain solution A, and at the same time, dissolving 9g of dimethylimidazole in 140mL of deionized water to obtain solution B, then quickly pouring solution B into solution A for mixing to obtain solution C, then stirring solution C at a stirring temperature of 25°C for a stirring time of 20min, finally, washing and centrifuging the obtained product with deionized water and anhydrous ethanol, and then vacuum drying at a drying temperature of 60°C for a drying time of 12h to obtain Cube-ZIF-67 with a hexahedral structure, referred to as C-ZIF-67;

[0058] In order to prove the composition of C-ZIF-67, XRD test was performed. The test results are shown in Figure 1 As shown, C-ZIF-67 has the characteristic peaks of ZIF-67. The test results show that step 1 successfully prepared ZIF-67.

[0059] In order to verify the microstructure of C-ZIF-67, SEM test was performed. Figure 3 As shown, C-ZIF-67 has a regular hexahedral structure with a smooth surface and a particle size of 0.5-1 μm.

[0060] In order to prove the electrochemical performance of C-ZIF-67, the electrochemical performance test was performed on the C-ZIF-67 obtained in step 1. The specific method of the electrochemical performance test is to perform the electrochemical performance test in a three-electrode system consisting of the material to be tested as the working electrode, the mercuric oxide electrode as the reference electrode, the platinum sheet electrode as the counter electrode, and the 6M KOH solution as the electrolyte. The electrochemical performance test results of C-ZIF-67 are shown in Figure 2. Fig. 9 As shown, charging and discharging in the range of 0-0.5V, at a current density of 1A -1 When the mass specific capacitance of C-ZIF-67 is 51 F g -1 .

[0061] Step 2, preparation of hollow hexahedral CH-CoS, first, dissolving 0.08 g of C-ZIF-67 obtained in step 1 in ethanol to obtain solution D, then adding 0.12 g of thioacetamide to solution D, performing hydrothermal reaction at a hydrothermal temperature of 120° C. for 4 h, sulfurizing and etching C-ZIF-67, and after the hydrothermal reaction is completed, vacuum drying the hydrothermal reaction product at a drying temperature of 60° C. for 12 h to obtain Cube-Hollow-Co3S4 with a hollow hexahedral structure, referred to as CH-CoS;

[0062] In order to prove the composition of CH-CoS, XRD test was carried out. The test results are as follows Figure 1 As shown, CH-CoS has the characteristic peak of Co3S4. Compared with the test results of step 1, it can be seen that C-ZIF-67 is converted into CH-CoS through the sulfurization of step 2.

[0063] In order to verify the microstructure of CH-CoS, SEM test was performed. The test results are shown in Figure 4 As shown, the basic microstructure of CH-CoS still maintains a regular hexahedral structure, but CH-CoS becomes a hollow structure. Compared with the test results of step 1, it can be seen that the microstructure of C-ZIF-67 is transformed into a hollow structure through etching in step 2, that is, the microstructure of CH-CoS is a hollow regular hexahedral structure.

[0064] Based on the XRD test and SEM test results, it can be seen that sulfurization and etching are achieved simultaneously through step 2.

[0065] In order to verify the pore size distribution and specific surface area of ​​CH-CoS, BET test was performed. The test results are shown in Figure 7 and Figure 8 As shown, the specific surface area of ​​CH-CoS is 21.95 m 2 g -1 , the pore size distribution is 4-6.5nm.

[0066] In order to prove the electrochemical performance of CH-CoS, electrochemical performance tests were carried out. The test results are shown in Fig. 9 As shown, the charge and discharge voltage range is 0-0.5V, and the current density is 1A g -1 Under the condition of -1 Compared with the test results of step 1, it can be seen that the mass specific capacitance of CH-CoS can be significantly improved by sulfurization and etching in step 2, with an improvement of 549%.

[0067] In order to prove the cycle performance of CH-CoS, a cycle performance test was carried out. The test results are shown in Fig.10 As shown, at a current density of 10Ag -1 , under the condition of 5000 cycles, 50% of the initial specific capacitance is retained.

[0068] Step 3, preparation of CH-CoS / NiOH, first, dissolving 0.05 g of CH-CoS obtained in step 2 in 60 mL of deionized water to obtain solution E, then adding 0.06 g of nickel nitrate hexahydrate and 0.06 g of urea to solution E and stirring to obtain solution F, then subjecting solution F to a hydrothermal reaction at a hydrothermal temperature of 120° C. for a hydrothermal time of 6 h, and after the hydrothermal reaction is completed, vacuum drying the hydrothermal reaction product at a drying temperature of 60° C. for a drying time of 12 h to obtain CH-CoS / NiOH;

[0069] Step 4, preparation of hollow hexahedral structure CH-CoS / NiO, calcining the CH-CoS / NiOH obtained in step 3 under air conditions at a calcination temperature of 300° C. and a calcination time of 2 h to obtain a hollow hexahedral structure cobalt sulfide loaded nickel oxide composite material CH-CoS / NiO, referred to as CH-CoS / NiO.

[0070] In order to prove the composition of CH-CoS / NiO, XRD test was carried out. The test results are as follows Figure 1 As shown, CH-CoS / NiO has characteristic peaks of Co3S4 and NiO at the same time. Compared with the test results of step 2, it can be seen that NiO is loaded on the surface of CH-CoS through the hydrothermal reaction of step 3 and the calcination of step 4, that is, CH-CoS / NiO is successfully prepared.

[0071] In order to further prove the composition of CH-CoS / NiO, XPS test was carried out. The test results are as follows Figure 2 As shown in the XPS total spectrum, the characteristic peaks of Ni, Co, O and S elements exist simultaneously, and the spectrum shows that CH-CoS / NiO contains Ni 2+ 、Ni 3+ 、Co 2 + , metal hydrogen bond and -OH bond. The XPS test results are consistent with the XRD test, indicating that CH-CoS / NiO was successfully prepared.

[0072] In order to verify the microstructure of CH-CoS / NiO, SEM test was carried out. The test results are shown in Figure 5 As shown, the basic microstructure of CH-CoS / NiO still maintains a hollow hexahedron structure, and nanoparticles grow on the smooth surface of the hollow hexahedron. Combined with the XRD test results, it can be seen that the hollow hexahedron structure is CH-CoS and the nanoparticles are NiO, that is, NiO nanoparticles are successfully loaded on the surface of CH-CoS through the hydrothermal reaction in step 3 and the calcination in step 4.

[0073] In order to further prove the microstructure of CH-CoS / NiO, that is, the hollow structure, TEM test and EDS test were carried out. The test results are as follows Figure 6 As shown, CH-CoS / NiO has a hollow structure, and Ni, Co, O, S, N and P elements are evenly distributed on the surface of CH-CoS / NiO.

[0074] In order to verify the pore size distribution and specific surface area of ​​CH-CoS / NiO, BET test was performed. The test results are shown in Figure 7 and Figure 8As shown, the specific surface area of ​​CH-CoS / NiO is 50.43 m 2 g -1 , the pore size distribution is 1.4-9.6nm. Compared with the test results of step 2 and the SEM test results, it can be seen that the specific surface area can be significantly increased by 229% through the hydrothermal reaction of step 3 and the calcination of step 4, and the pore size distribution range becomes larger, that is, the pore structure is richer.

[0075] In order to prove the electrochemical performance of CH-CoS / NiO, electrochemical performance tests were carried out. The test results are shown in Fig. 9 As shown, the charge and discharge voltage range is 0-0.5V, and the current density is 1A g -1 Under the condition of -1 Compared with the test results of step 2, it can be seen that the mass specific capacitance can be significantly improved by the hydrothermal reaction of step 3 and the calcination of step 4, with an improvement of 435%.

[0076] In order to prove the cycle performance of CH-CoS / NiO, a cycle performance test was carried out. The test results are as follows Fig.10 As shown, at a current density of 10Ag -1 , under the condition of 5000 cycles, 83.4% of the initial specific capacitance is retained. Compared with the test results of step 2, it can be seen that the cycle performance can be significantly improved through the hydrothermal reaction in step 3 and the calcination in step 4.

[0077] In order to further prove the electrochemical performance of CH-CoS / NiO, a double electrode test was performed. The test results are shown in Fig.11 As shown in the figure, the supercapacitor device assembled with CH-CoS / NiO and activated carbon as electrodes has a high conductivity at 800 W kg -1 The power density was 36.74Wh kg -1 energy density.

[0078] By comparing CH-CoS and CH-CoS / NiO, the role of NiO in the technical solution can be demonstrated. The specific role is that NiO grows on the surface of CH-CoS to form a composite structure, promotes the transmission of ions, and improves the Faradaic redox reaction of the composite material as a whole. Therefore, the specific capacitance performance of CH-CoS / NiO is enhanced.

[0079] In order to demonstrate step 1 of the preparation method, namely the effect of micromorphology on performance, comparative example 1 is provided, a ZIF-67 with a regular dodecahedral structure.

[0080] Comparative Example 1

[0081] A method for preparing ZIF-67 with a regular dodecahedral structure adopts a conventional ZIF-67 preparation method, specifically, the steps not specified are the same as those in Example 1, except that: in the step 1, hexadecyltrimethylammonium bromide is not added, and the stirring time is extended to 2 hours. Step 1 can obtain Dodecahedron-ZIF-67 with a regular dodecahedral structure, referred to as D-ZIF-67.

[0082] In order to prove the composition of D-ZIF-67, XRD test was carried out. The test results are shown in Figure 1 As shown, D-ZIF-67 has characteristic peaks of ZIF-67. Compared with C-ZIF-67 of Example 1, it can be seen that D-ZIF-67 and C-ZIF-67 have the same composition, that is, the preparation method has no effect on the composition.

[0083] In order to verify the microstructure of D-ZIF-67, SEM test was performed. Fig.12 As shown, D-ZIF-67 is a regular dodecahedron structure with a smooth surface and a particle size of 0.4-0.6 μm. Compared with C-ZIF-67 in Example 1, it can be seen that by adding hexadecyltrimethylammonium bromide and controlling the stirring time, the morphology of ZIF-67 can be changed and the particle size of ZIF-67 can be regulated, that is, the preparation method has a substantial effect on the morphology.

[0084] In order to prove the electrochemical performance of D-ZIF-67, electrochemical performance tests were carried out. The test results are shown in Fig.13 As shown, the charge and discharge are carried out in the range of 0-0.5V and the current density is 1A g -1 When the mass specific capacitance of D-ZIF-67 is 32 F g -1 Compared with C-ZIF-67 in Example 1, it can be seen that the change of the microstructure of ZIF-67 from a regular dodecahedron structure to a regular hexahedron structure can significantly improve the mass specific capacitance by 59.4%. The test results show that the microstructure of ZIF-67 has a significant impact.

[0085] It can be seen from Comparative Example 1 and Example 1 that by changing the preparation method, the microstructure and particle size of ZIF-67 can be regulated, thereby significantly improving the electrochemical performance.

[0086] In order to demonstrate step 2 of the preparation method, namely the effect of micromorphology on performance, comparative example 2 is provided, which is a NiCo-LDH prepared based on Ni(NO3)2·6H2O etching.

[0087] Comparative Example 2

[0088] A NiCo-LDH prepared based on Ni(NO3)2·6H2O etching, wherein the steps without particular description are the same as those in Example 1, except that in step 2, Ni(NO3)2·6H2O is used instead of thioacetamide to etch ZIF-67, and the obtained material is referred to as NiCo-LDH.

[0089] In order to verify the microstructure of NiCo-LDH, SEM test was performed. The test results are shown in Fig.14 As shown, the microscopic morphology of NiCo-LDH is a particle structure with stacked flakes on the surface, and the particle size is 0.5-1.2 μm. Compared with C-ZIF-67 in Example 1, it can be seen that using Ni(NO3)2·6H2O as an etching agent will destroy the microscopic morphology of ZIF-67 and cannot achieve the technical effect of etching to obtain a hollow structure.

[0090] In order to prove the electrochemical performance of NiCo-LDH, electrochemical performance tests were carried out. The electrochemical performance test results of NiCo-LDH are shown in Fig.15 As shown, charging and discharging in the range of 0-0.5V, at a current density of 1A -1 When the mass specific capacitance of NiCo-LDH is 1150F g -1 .

[0091] Compared with the CH-CoS / NiO of Example 1, it can be seen that the mass specific capacitance achieved by etching with thioacetamide to obtain a hollow hexahedral structure and then loading the Ni element is better than that achieved by etching with Ni(NO3)2·6H2O;

[0092] In order to further analyze the role of obtaining a hollow hexahedral structure by etching with thioacetamide, it can be seen from the comparison with C-ZIF-67 in Example 1 that etching with Ni(NO3)2·6H2O can significantly improve the mass specific capacitance; further compared with CH-CoS in Example 1, it can be seen that the improvement effect is better than thioacetamide, and the mass specific capacitance is 410.7% of that of CH-CoS;

[0093] The reason is that Ni(NO3)2·6H2O can load Ni during etching, i.e., prepare NiCo-LDH.

[0094] However, according to the inventor's experience, during the etching process, the microscopic morphology of the material is converted into a sheet-like stacked structure of NiCo-LDH, which will lead to structural collapse during the charge and discharge cycle, resulting in poor cycle performance.

[0095] Therefore, in order to further prove the cycle performance of NiCo-LDH, a cycle performance test was carried out. The cycle performance test results of NiCo-LDH are shown in Fig.10As shown, at a current density of 10Ag -1 , under the condition of 1000 cycles, 75.3% of the initial specific capacitance is retained.

[0096] By comparing the cycle performance of CH-CoS / NiO with that of Example 1, the above judgment can be proved, that is, etching ZIF-67 with thioacetamide to obtain a hollow hexahedral structure and then loading the Ni element can not only significantly improve the mass specific capacitance, but also obtain a stable material structure and improve the cycle stability of the material.

[0097] It can be seen from Comparative Example 2 and Example 1 that using different raw materials for etching will produce different microscopic morphologies and thus obtain different electrochemical properties.

[0098] The following conclusions can be drawn from the above experiments:

[0099] 1. The high electrochemical performance of CH-CoS / NiO is achieved by combining the high electrochemical activity of CH-CoS and NiO nanoparticles;

[0100] 2. By loading NiO nanoparticles on CH-CoS, the specific surface area of ​​the composite material is effectively increased, the active sites are increased, and ultimately the mass specific capacitance performance is significantly improved.

Claims

1. A hollow hexahedral cobalt sulfide-loaded nickel oxide composite material, characterized in that: Taking the hexahedral C-ZIF-67 as the substrate, it was first etched by a solvothermal method to convert it into a hollow hexahedral cobalt sulfide CH-CoS, and then nickel oxide nanoparticles NiO were loaded on the hollow hexahedral cobalt sulfide CH-CoS by a solvothermal method and calcination to obtain CH-CoS / NiO.

2. The hollow hexahedral cobalt sulfide-loaded nickel oxide composite material according to claim 1, characterized in that: The microstructure of the C-ZIF-67 is a regular hexahedron structure, the microstructure of the CH-CoS is a hollow regular hexahedron structure; the microstructure of the CH-CoS / NiO is a hollow regular hexahedron structure, and nickel oxide particles are loaded on the surface.

3. The hollow hexahedral cobalt sulfide-loaded nickel oxide composite material according to claim 1, characterized in that: The specific surface area of ​​CH-CoS is 15-25m 2 g -1 The pore size distribution is 4-6.5 nm, and the specific surface area of ​​CH-CoS / NiO is 45-55 m 2 g -1 , the pore size distribution is 1.4-9.6nm.

4. A method for preparing a hollow hexahedral cobalt sulfide-loaded nickel oxide composite material, characterized in that The following steps are involved: Step 1, preparation of ZIF-67 with a regular hexahedral structure, first, dissolving cobalt nitrate hexahydrate and hexadecyltrimethylammonium bromide in deionized water to obtain a solution A, and at the same time, dissolving dimethylimidazole in deionized water to obtain a solution B, then quickly pouring the solution B into the solution A for mixing to obtain a solution C, then stirring the solution C under certain conditions, and finally, washing and centrifuging the obtained product with deionized water and anhydrous ethanol, and then vacuum drying under certain conditions to obtain Cube-ZIF-67 with a regular hexahedral structure, referred to as C-ZIF-67; Step 2, preparation of hollow hexahedral CH-CoS, first, dissolving the C-ZIF-67 obtained in step 1 in ethanol to obtain a D solution, then adding thioacetamide to the D solution, performing a hydrothermal reaction under certain conditions, sulfiding and etching the C-ZIF-67, and after the hydrothermal reaction is completed, vacuum drying the hydrothermal reaction product under certain conditions to obtain a hollow hexahedral Cube-Hollow-Co3S4, referred to as CH-CoS; Step 3, preparation of CH-CoS / NiOH, first, dissolving the CH-CoS obtained in step 2 in deionized water to obtain solution E, then adding nickel nitrate hexahydrate and urea to solution E and stirring sufficiently to obtain solution F, then subjecting solution F to a hydrothermal reaction under certain conditions, and after the hydrothermal reaction is completed, vacuum drying the hydrothermal reaction product under certain conditions to obtain CH-CoS / NiOH; Step 4, preparation of hollow hexahedral CH-CoS / NiO. Under certain conditions, the CH-CoS / NiOH obtained in step 3 is calcined to obtain a hollow hexahedral cobalt sulfide-loaded nickel oxide composite material CH-CoS / NiO, referred to as CH-CoS / NiO.

5. The preparation method according to claim 4, characterized in that: In the step 1, the mass ratio of aqueous cobalt nitrate, hexadecyltrimethylammonium bromide and dimethylimidazole is 60:1:900; In the step 2, the mass ratio of C-ZIF-67 to thioacetamide is 1:1.5; In step 3, the mass ratio of CH-CoS, nickel nitrate hexahydrate and urea is 5:6:

6.

6. The preparation method according to claim 4, characterized in that: In step 1, the stirring conditions are as follows: the stirring temperature is 20-30°C and the stirring time is 10-30min; the drying conditions are as follows: the drying temperature is 50-70°C and the drying time is 11-13h; In step 2, the conditions for the hydrothermal reaction are: the hydrothermal temperature is 110-130° C., and the hydrothermal time is 3-5 hours; the conditions for the drying are: the drying temperature is 50-70° C., and the drying time is 11-13 hours; In step 3, the conditions for the hydrothermal reaction are: the hydrothermal temperature is 110-130° C., and the hydrothermal time is 5-7 hours; the conditions for the drying are: the drying temperature is 50-70° C., and the drying time is 11-13 hours; In step 4, the calcination conditions are: in air, the calcination temperature is 200-400° C., and the calcination time is 1-3 hours.

7. The hollow hexahedral cobalt sulfide-loaded nickel oxide composite material according to claim 4, characterized in that: When used as a supercapacitor electrode material, it is charged and discharged in the voltage window range of 0-0.5V, and the current density is 1Ag -1 When the mass specific capacitance is 1200-1300F g -1 .

8. The hollow hexahedral cobalt sulfide-loaded nickel oxide composite material according to claim 4, characterized in that: When used as a supercapacitor electrode material, the current density is 10A. -1 When the battery is charged and discharged for 5,000 times, it still retains 80-90% of its initial capacity.

9. The hollow hexahedral cobalt sulfide-loaded nickel oxide composite material according to claim 4, characterized in that: When used as a supercapacitor device assembled with activated carbon, the power density is 800W kg -1 The energy density is 30-40Wh kg -1 .

Citation Information

Patent Citations

  • Preparation method and application of zinc cobaltate / nickel oxide core-shell nanowire array

    CN103956483A

  • Metallic oxide / metal sulfide hollow nanospheres as well as preparation method and application thereof

    CN104492460A

  • Preparation method of ellipsoidal Fe2O3 / NiO nanocomposite material

    CN107352588A

  • Supercapacitor electrode material and preparation method thereof

    CN107785181A

  • Preparation method and application of ternary metal composite oxide with ZIF-8 compounded ZIF-67 as template

    CN110182859A